2019
DOI: 10.3390/ijms20194687
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exo-miRNAs in Cancer: A Focus on Therapeutic and Diagnostic Applications

Abstract: Exosomes are extracellular vesicles released into biological fluids where they act as carriers of various molecules, including proteins, lipids, and RNAs, between cells, modulating or perturbing specific physiological processes. Recently, it has been suggested that tumoral cells release excessive amounts of exosomes that, through their cargo, promote tumor progression, stimulating growth, angiogenesis, metastasis, insensitivity to chemotherapy, and immune evasion. Increasing evidence highlights exosomal microR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 111 publications
(105 reference statements)
0
83
0
1
Order By: Relevance
“…Little is known about the miR-216a regulation in cancer, but a recent manuscript by Tao W and colleagues reported that a long noncoding RNA named DANCR is able to target miR-216a-5p in breast cancer, regulating the expression of stemness markers such as Nanog, SOX2 and OCT4 [12].The tumor microenvironment is largely involved in the regulation of neoplastic processes; it includes cells belonging to innate immunity, such as macrophages, neutrophils, and mast cells, and to adaptive immunity, such as T and B lymphocytes as well as stromal cells (fibroblasts, endothelial cells and mesenchymal cells) [13][14][15]. All these components of the tumor microenvironment interact with each other and cancer cells by either direct contact or through the release of cytokines and chemokines, which can act as paracrine or autocrine effectors [16][17][18]. The level of activation of these different cell types and the relative expression of the various mediators are able to tilt the balance in favor or against cancer progression [19,20].Through modulation of gene expression related to the inflammation, miRNAs influence cancer-related inflammation, enhancing cancer tumorigenicity and aggressiveness.…”
mentioning
confidence: 99%
“…Little is known about the miR-216a regulation in cancer, but a recent manuscript by Tao W and colleagues reported that a long noncoding RNA named DANCR is able to target miR-216a-5p in breast cancer, regulating the expression of stemness markers such as Nanog, SOX2 and OCT4 [12].The tumor microenvironment is largely involved in the regulation of neoplastic processes; it includes cells belonging to innate immunity, such as macrophages, neutrophils, and mast cells, and to adaptive immunity, such as T and B lymphocytes as well as stromal cells (fibroblasts, endothelial cells and mesenchymal cells) [13][14][15]. All these components of the tumor microenvironment interact with each other and cancer cells by either direct contact or through the release of cytokines and chemokines, which can act as paracrine or autocrine effectors [16][17][18]. The level of activation of these different cell types and the relative expression of the various mediators are able to tilt the balance in favor or against cancer progression [19,20].Through modulation of gene expression related to the inflammation, miRNAs influence cancer-related inflammation, enhancing cancer tumorigenicity and aggressiveness.…”
mentioning
confidence: 99%
“…Accumulating evidence indicates not only the importance of miRNAs as molecular players in tumorigenesis, but also their valuable diagnostic and therapeutic applications. The term "exo-miRNAs" has been coined to describe miRNAs that are stored in cellular exosomes and released into biological fluids, where they can be easily detected due to their high stability to provide more precise diagnoses and more personalized therapeutic strategies [283].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, tumor cells secrete higher quantities of exosomes than normal cells, and tumor cells derived exosomes promote tumor progression by inducing malignant transformation in normal cells, tumor escape to immune system, CAF transformation, angiogenesis and metastasis [7]. Hence, efforts are being made to inhibit tumor cells derived exosomes release and uptake [145]. Interestingly, silencing in melanoma cells of Rab27, a protein involved in the transport of the late endosome from the nucleus to the plasmatic membrane, induced miR-494 accumulation, with consequent suppression of malignant phenotype by apoptosis induction [11].…”
Section: Targeting Tumor Cells Derived Exosomesmentioning
confidence: 99%